2006
DOI: 10.1143/jjap.45.l1030
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Step-Like Output Energy Decrease Observed in an ArF Excimer Laser for Microlithography

Abstract: A step-like decrease of the output energy of an ArF excimer laser for microlithography has been observed during highrepetition rate and high-power operation. The reason for the step-like energy decrease was traced to oxygen by adding 50 ppm of various gas impurities to the laser gas. It is supposed that the energy decrease is caused by laser light absorption due to the oxygen or to some kinds of oxygen compounds because no change was observed in ArF and XeF emission intensities which were monitored as measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Various tests [12][13][14] concerning the steplike energy decrease of the ArF excimer laser confirmed that the energy recovers after a rest time of approximately 0.2 s during burst operation, and that the ratio of the decrease in the energy decreases with increasing gas temperature. Because the absorbing compound F x O y is unstable, its dissociation time and the dependences of its concentration on gas temperature and initial oxygen concentration were investigated.…”
Section: Temporal Variations In Absorption At 193 Nm For Different Ga...mentioning
confidence: 92%
See 1 more Smart Citation
“…Various tests [12][13][14] concerning the steplike energy decrease of the ArF excimer laser confirmed that the energy recovers after a rest time of approximately 0.2 s during burst operation, and that the ratio of the decrease in the energy decreases with increasing gas temperature. Because the absorbing compound F x O y is unstable, its dissociation time and the dependences of its concentration on gas temperature and initial oxygen concentration were investigated.…”
Section: Temporal Variations In Absorption At 193 Nm For Different Ga...mentioning
confidence: 92%
“…In our previous study 14) involving passive spectroscopic observations, we reported that the steplike decrease in the output energy of the ArF excimer laser is caused by laser light absorption and not by a decrease in laser gain. Also, we revealed that oxygen causes the steplike energy decrease.…”
Section: Introductionmentioning
confidence: 90%